2023
DOI: 10.1038/s41536-022-00274-z
|View full text |Cite
|
Sign up to set email alerts
|

In-situ forming injectable GFOGER-conjugated BMSCs-laden hydrogels for osteochondral regeneration

Abstract: The collagen-mimetic peptide GFOGER possesses the chondrogenic potential and has been used as a cell adhesion peptide or chondrogenic inducer. Here, we prepared an injectable in situ forming composite hydrogel system comprising methoxy polyethylene glycol-b-polycaprolactone (MPEG-PCL) and GFOGER-conjugated PEG-PCL (GFOGER-PEG-PCL) with various GFOGER concentrations based on our recently patented technology. The conjugation of GFOGER to PEG-PCL was confirmed by 1H NMR, and the particle size distribution and rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…MSCs are capable of differentiation into osteoblasts, adipocytes, and chondrocytes and chondrogenic differentiation is regulated by various factors. 66 Previous study has demonstrated that sEV isolated from MSCs increase the expression of cartilage ECM components and promote cartilage repair. 67 Our experiments have demonstrated that MT-sEV have a stronger ability to promote chondrogenic differentiation of BMSCs and to enhance matrix synthesis of chondrocytes compared with sEV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs are capable of differentiation into osteoblasts, adipocytes, and chondrocytes and chondrogenic differentiation is regulated by various factors. 66 Previous study has demonstrated that sEV isolated from MSCs increase the expression of cartilage ECM components and promote cartilage repair. 67 Our experiments have demonstrated that MT-sEV have a stronger ability to promote chondrogenic differentiation of BMSCs and to enhance matrix synthesis of chondrocytes compared with sEV.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs migrate to the damaged site and differentiate into chondrocytes after cartilage injury, which is beneficial for cartilage regeneration. MSCs are capable of differentiation into osteoblasts, adipocytes, and chondrocytes and chondrogenic differentiation is regulated by various factors 66 . Previous study has demonstrated that sEV isolated from MSCs increase the expression of cartilage ECM components and promote cartilage repair 67 .…”
Section: Discussionmentioning
confidence: 99%
“…175 Moreover, Ha et al developed an in situ -gelation injectable hydrogel consisting of methoxy polyethylene glycol- b -polycaprolactone (MPEG-PCL) and collagen-mimetic peptide GFOGER-conjugated PEG-PCL (GFOGER-PEG-PCL). 176 Owing to the added GFOGER, it significantly increased the expression of integrins and FAK, and induced downstream signaling of p38 and ERK, which finally exhibited remarkable promotion of osteochondral regeneration.…”
Section: Fabrication Of Injectable Hydrogelsmentioning
confidence: 96%
“…For example, QHREDGS (Q) peptide hydrogel has been shown to improve wound healing by increasing keratinocyte migration and the stimulation of neovascularization . Recently, the collagen-mimetic peptide GFOGER has been used as a chondrogenic inducer . Incorporation of this peptide into hydrogel resulted in the retention of bone marrow-derived mesenchymal stem cells, providing a platform for further research into osteochondral regeneration .…”
Section: Moving Forwardmentioning
confidence: 99%